Gender violence in Ecuador: A study about university students (2017)
Several of the Latin American countries present some of the highest figures in the world on gender violence: historical, cultural, political and socio-economic circumstances strongly determine the construction of the imaginary where gender supremacy prevails, such as in Ecuador, a context in which, according to official figures, six out of ten women are victims of some kind of violence. In this article, we present the results of a project comprising almost three thousand surveys from a reference group of university students. Broadly speaking, there has been a lack of awareness -especially among men- of the complexity due to the phenomenon of violence, as well as a certain tolerance towards this type of social epidemic. Therefore, institutional authorities should intensify strategic communication campaigns to promote an erosion of the symbolic factors that motivate the persistence of a residual traditionalism in this significant epicenter of the Andean culture.